Analisis Jaringan Komunikasi #WAJARPERTAMAKNAIK Dalam Kasus Kenaikan Harga Bahan Bakar Pertamax Di Twitter - Andra Ramadhan; Eko Hartanto (Peneliti.net, 2023)
This research aims to find out the relationship between actors in the analysis of communication networks at the actor level and what tweets or tweets are discussed on #WajarPertamaxNaik via Twitter social media. The methods in this study used quantitative methods. The technique used in this study is with Social Network Analysis (SNA), by crawling data using the Netlytic.org website and results to examine relational data not just on the characteristics of individual actors' attributes, and focusing on explaining the patterns between actors, and analyzing the structures of patterns by using them. It's a gephi application. The study's population was 2500 Twitter followers with #WajarPertamaxNaik on April 1, 2022 and a sample of 1074 actors (nodes) were collected on data crawling and data processing. The theory used in this study is Computer Mediated Communication Theory (CMC), Political Communication and Social Media. Research results show that the cybsquad_account is the highest actor popularity, account 13_udien is the closest proximity actor between actor one and actor, actor in law-law is the aerospace centrality actor who becomes the communications liaison actor. There are different communication networks, and the actor cybsquad_ is the actor of eigenvector centrality who becomes an important actor in communication networks with other actors .